Cases on strategic partnerships for resilient communities and schools - Thomas, Ursula 1972- (IGI Global, 2020)
"This book explores the complex relationship between schools, communities, non-profit organizations, and businesses in an effort to examine the intersection of how we can best support school populations that are traditionally marginalized or underserved in rural and urban areas"--